Multiple Lines of Evidence for a Potentially Seismogenic Fault Along the Central-Apennine (Italy) Active Extensional Belt–An Unexpected Outcome of the MW6.5 Norcia 2016 Earthquake - Ferrarini, Federica; de Nardis, Rita; Brozzetti, Francesco; Cirillo, Daniele; Arrowsmith, J Ramón; Lavecchia, Giusy (Frontiers in Earth Science, 2021)
The Apenninic chain, in central Italy, has been recently struck by the Norcia 2016 seismic sequence. Three mainshocks, in 2016, occurred on August 24 (MW6.0), October 26 (MW 5.9) and October 30 (MW6.5) along well-known late Quaternary active WSW-dipping normal faults. Coseismic fractures and hypocentral seismicity distribution are mostly associated with failure along the Mt Vettore-Mt Bove (VBF) fault. Nevertheless, following the October 26 shock, the aftershock spatial distribution suggests the activation of a source not previously mapped beyond the northern tip of the VBF system. In this area, a remarkable seismicity rate was observed also during 2017 and 2018, the most energetic event being the April 10, 2018 (MW4.6) normal fault earthquake. In this paper, we advance the hypothesis that the Norcia seismic sequence activated a previously unknown seismogenic source. We constrain its geometry and seismogenic behavior by exploiting: 1) morphometric analysis of high-resolution topographic data; 2) field geologic- and morphotectonic evidence within the context of long-term deformation constraints; 3) 3D seismological validation of fault activity, and 4) Coulomb stress transfer modeling. Our results support the existence of distributed and subtle deformation along normal fault segments related to an immature structure, the Pievebovigliana fault (PBF). The fault strikes in NNW-SSE direction, dips to SW and is in right-lateral en echelon setting with the VBF system. Its activation has been highlighted by most of the seismicity observed in the sector. The geometry and location are compatible with volumes of enhanced stress identified by Coulomb stress-transfer computations. Its reconstructed length (at least 13 km) is compatible with the occurrence of MW≥6.0 earthquakes in a sector heretofore characterized by low seismic activity. The evidence for PBF is a new observation associated with the Norcia 2016 seismic sequence and is consistent with the overall tectonic setting of the area. Its existence implies a northward extent of the intra-Apennine extensional domain and should be considered to address seismic hazard assessments in central Italy.